Cardiovascular Prevention of Cognitive Decline - Jean-Jacques Monsuez; Aude Gesquière-Dando; Sofia Rivera (Cardiology Research and Practice)
Midlife cardiovascular risk factors, including diabetes, hypertension, dyslipemia, and an unhealthy lifestyle, have been linked to subsequent incidence, delay of onset, and progression rate of Alzheimer disease and vascular dementia. Conversely, optimal treatment of cardiovascular risk factors prevents and slows down age-related cognitive disorders. The impact of antihypertensive therapy on cognitive outcome in patients with hypertension was assessed in large trials which demonstrated a reduction in progression of MRI white matter hyperintensities, in cognitive decline and in incidence of dementia. Large-scale database correlated statin use and reduction in the incidence of dementia, mainly in patients with documented atherosclerosis, but clinical trials failed to reach similar conclusions. Whether a multitargeted intervention would substantially improve protection, quality of life, and reduce medical cost expenditures in patients with lower risk profile has not been ascertained. This would require appropriately designed trials targeting large populations and focusing on cognitive decline as a primary outcome endpoint.